Processos de criação na obra de Maya Watanabe - Furtado, Sylvia Beatriz Bezerra (2016)
The article explores the creative processes in some works of Maya Watanabe, in particular transactions that involve cinema and visual arts. The research, the investigation field, the passage to the desk, the development of the work and the way to expose the screens in space. Maya Watanabe thinks the space, the picture, the scene, the assembly, the dimension of language, time and narrative as composition of the work force